Beyond professional boundaries: relationships and resources in health services' modernisation in England and Wales. Issue 3 (25th November 2013) - Huby, Guro; Harris, Fiona M; Powell, Alison E.; Kielman, Tara; Sheikh, Aziz; Williams, Sian; Pinnock, Hilary
Abstract This article draws on theories of social capital to understand ways in which the negotiation of professional boundaries among healthcare professionals relates to health services change. We compared reconfiguration of respiratory services in four primary care organisations (PCOs) in England and Wales. Service development was observed over 18 months during a period of market‐based reforms. Serial interviews with key clinicians and managers from hospital trusts and PCOs followed progress as they collaborated around, negotiated and contested developments. We found that professionals work to protect and expand their claims to work territory. Remuneration and influence was a catalyst for development and was also necessary to establish professional boundaries that underpinned novel service arrangements. Conflict and contest was less of a threat to change than a lack of engagement in boundary work because this engagement produced relationships based on forming shifting professional allegiances across and along boundaries, and these relationships mediated the social capital needed to accomplish change. However, this process also (re)produced inequalities among professions and prevented some groups from participation in service change.